2021
DOI: 10.1002/cbin.11633
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA DANCR improves the dysfunction of the intestinal barrier and alleviates epithelial injury by targeting the miR‐1306‐5p/PLK1 axis in sepsis

Abstract: Intestinal barrier dysfunction often occurs in various acute or chronic pathological conditions and has been identified as an important clinical problem. Herein, we explored the biological role and molecular mechanism of Polo‐like kinase 1 (PLK1) and differentiation antagonizing non‐protein coding RNA (DANCR) in intestinal barrier dysfunction caused by sepsis. RT‐qPCR analysis was used to examine PLK1, miR‐1306‐5p, and DANCR expression in NCM460 cells after LPS treatment. TUNEL assay and Western blot analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Several miRNAs are also found to play crucial roles in AML by regulating various kinds of biological processes, such as miRNA-485-5p, miR-126, and miR-204 [12][13][14]. In addition, as reported previously, miR-1306-5p is involved in the progression of many diseases, such as amelogenesis imperfecta, cerebral ischemia/reperfusion injury, and sepsis [15][16][17]. However, the role of miR-1306-5p in AML is obscure.…”
Section: Introductionmentioning
confidence: 82%
“…Several miRNAs are also found to play crucial roles in AML by regulating various kinds of biological processes, such as miRNA-485-5p, miR-126, and miR-204 [12][13][14]. In addition, as reported previously, miR-1306-5p is involved in the progression of many diseases, such as amelogenesis imperfecta, cerebral ischemia/reperfusion injury, and sepsis [15][16][17]. However, the role of miR-1306-5p in AML is obscure.…”
Section: Introductionmentioning
confidence: 82%
“…An increasing amount of evidence indicated that lncRNAs can influence cellular functions by regulating mRNAs through adsorption of corresponding miRNAs [ 51 ]. lncRNA DANCR targeting miR-1306-5p/polo-like Kinase 1 ( PLK1 ) axis reduced intestinal mucosal permeability and apoptosis of colonic mucosal epithelial cells and improved intestinal barrier dysfunction [ 52 ]. lncRNA TUG1 overexpression, targeting the miR-186-5p/X-linked inhibitor of apoptosis protein ( XIAP ) axis, attenuated NLRP3 inflammatory vesicle-induced cardiomyocyte scorching [ 53 ].…”
Section: Discussionmentioning
confidence: 99%